1966
DOI: 10.1136/gut.7.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and coincidence of hiatus hernia.

Abstract: The frequency of hiatus hernias found incidentally during routine barium meal examinations has been reported on many occasions (Eisen, 1938;Levy and Duggan, 1941;Mendelsohn, 1946;Root and Pritchett, 1938;and Ritvo, 1930), and varies between 0-8% and 2-9%. When the abdominal pressure is increased by any method during the examination, the incidence rises to between 2-1% and 11 8% (Boyd, Harris, Butler, and Donaldson, 1956;Carmichael, 1959;Conway-Hughes, 1956;Sim, 1964;and Hafter, 1958). Stein and Finkelstein (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

1968
1968
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…Since the main conclusion results are not significant that may be drawn from a survey of the literature is t group complaining of other that the presence of a hiatus hernia bears an irregular series (p > 0.7 using the x2 relationship to the incidence of upper gastrointestinal hernia in the presence Of symptoms, the correlation of symptoms with other increased, radiological findings should be investigated. It has been shown that the size of the loculus is not related to symptoms (Hiebert and Belsey, 1961;Rex, BLE V Andersen, Bartholomew, and Cain, 1961) and this is PAIN AND HIATUS HERNIA also suggested by (Pridie, 1966) than in our 6 6 50 asymptomatic patients. Unfortunately, a suspension 13 7 35 of barium is more viscous than gastric juice and reflux may be demonstrated by pH measurements in the lower oesophagus in subjects who show no oU55ION radiological reflux (Hill, Chapman, and Morgan, 1961).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Since the main conclusion results are not significant that may be drawn from a survey of the literature is t group complaining of other that the presence of a hiatus hernia bears an irregular series (p > 0.7 using the x2 relationship to the incidence of upper gastrointestinal hernia in the presence Of symptoms, the correlation of symptoms with other increased, radiological findings should be investigated. It has been shown that the size of the loculus is not related to symptoms (Hiebert and Belsey, 1961;Rex, BLE V Andersen, Bartholomew, and Cain, 1961) and this is PAIN AND HIATUS HERNIA also suggested by (Pridie, 1966) than in our 6 6 50 asymptomatic patients. Unfortunately, a suspension 13 7 35 of barium is more viscous than gastric juice and reflux may be demonstrated by pH measurements in the lower oesophagus in subjects who show no oU55ION radiological reflux (Hill, Chapman, and Morgan, 1961).…”
Section: Resultssupporting
confidence: 74%
“…SEX Nearly twice as many men as women were Pridie (1966)' included in the study by chance, but the overall incidence of hernia in each sex was similar-33 % in men, 32 % in women. OBESITY As a rough guide to obesity, an index was calculated by dividing the weight of each patient by his height.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barrett's esophagus is the eponym applied to the columnar epithelium-lined lower esophagus that is acquired as a consequence of chronic gas troesophageal reflux [4] . Hiatus hernia, on the other hand, has been defined as a displacement of the gastric mucosa 1.5cm or more above the diaph ragmatic hiatus [5] .…”
Section: Definitionsmentioning
confidence: 99%